Diagnostic Challenges of Antiphospholipid Syndrome in Recurrent Pregnancy Loss: A Case Report - Ni Luh Lany Christina Prajawati; Artha Falentin Putri Susilo (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
Introduction: Recurrent pregnancy loss is a complex condition that affects a small number of women, with antiphospholipid syndrome being a well-recognized cause. Antiphospholipid syndrome is an autoimmune disorder associated with vascular thrombosis and pregnancy complications.Case report: We present a 23-year-old woman with four consecutive pregnancy losses and cerebral venous sinus thrombosis. Despite an initial inability to fully confirm APS using the Sydney criteria due to resource limitations that hindered repeated laboratory testing, consultation with the rheumatology department led to a diagnosis based on the European Alliance of Associations for Rheumatology and American College of Rheumatology (ACR/EULAR) 2023 criteria. This case highlights the diagnostic challenges of antiphospholipid syndrome, especially in low-resource settings where repeat laboratory testing is often not feasible, underscoring the importance of alternative classification systems for confirming antiphospholipid syndrome when standard criteria cannot be met. Further research is necessary to validate the ACR/EULAR 2023 classification criteria and evaluate their impact on pregnancy outcomes in patients.Conclusion: To optimize limited resources, improved diagnosis and pregnancy planning for patients with antiphospholipid syndrome and cerebral venous sinus thrombosis are achieved by applying current classification criteria along with multidisciplinary management, including anticoagulation and obstetric care.Tantangan Diagnosis Sindrom Antifosfolipid pada Keguguran Berulang: Sebuah Laporan KasusAbstrakPendahuluan: Keguguran berulang adalah kondisi multifaktorial yang memengaruhi sebagian kecil wanita, dengan sindrom antifosfolipid sebagai salah satu penyebab yang dikenal. Sindrom antifosfolipid adalah gangguan autoimun yang berhubungan dengan trombosis vaskular dan komplikasi kehamilan.Laporan kasus: Kami melaporkan seorang wanita berusia 23 tahun yang mengalami empat kali keguguran berturut-turut dan didiagnosis dengan trombosis sinus vena serebri. Meskipun pada awalnya konfirmasi penuh sindrom antifosfolipid, menurut kriteria Sydney tidak memungkinkan karena keterbatasan sumber daya yang menghambat pengulangan pemeriksaan laboratorium, konsultasi dengan bagian reumatologi menghasilkan diagnosis berdasarkan kriteria 2023 dari European Alliance of Associations for Rheumatology dan American College of Rheumatology (ACR/EULAR). Kasus ini menyoroti tantangan diagnostik sindrom antifosfolipid, terutama di lingkungan dengan sumber daya terbatas dengan pemeriksaan laboratorium berulang tidak selalu dapat dilakukan, serta pentingnya penggunaan sistem klasifikasi alternatif untuk menegakkan diagnosis ketika kriteria standar tidak dapat dipenuhi. Diperlukan penelitian lebih lanjut untuk memvalidasi kriteria klasifikasi ACR/EULAR 2023 dan menilai dampaknya terhadap hasil kehamilan pada pasien.Kesimpulan: Untuk mengoptimalkan sumber daya yang terbatas, penggunaan kriteria klasifikasi saat ini bersama perawatan antikoagulasi dan obstetri secara multidisipliner memungkinkan diagnosis dan perencanaan kehamilan yang lebih baik bagi pasien dengan sindrom antifosfolipid dan trombosis sinus vena serebral.